Mechanisms for Rapid Evolution of Carbapenem Resistance in a Clinical Isolate of Pseudomonas aeruginosa - Xu, Congjuan; Wang, Dan; Zhang, Xinxin; Liu, Huimin; Zhu, Guangbo; Wang, Tong; Cheng, Zhihui; Wu, Weihui; Bai, Fang; Jin, Yongxin (Frontiers in Microbiology, 2020)
Infections by Pseudomonas aeruginosa are often difficult to cure due to its high intrinsic and acquired antibiotic resistance. Once colonized in the human hosts, P. aeruginosa acquires genetic mutations which render the bacteria antibiotic resistance as well as ability to better adapt to the host environment. Deciphering the evolutionary traits may provide important insights into the development of effective combinatory antibiotic therapy to treat P. aeruginosa infections. In this study, we investigated the molecular mechanisms by which a clinical isolate (ISP50) yields to an imipenem-resistant derivative (IRP41). RNAseq and genomic DNA reference mapping were conducted to compare the transcriptional profiles and in vivo evolutionary trajectories between the two isolates. Our overexpression results demonstrated that oprD mutation together with ampC hyper-expression contributed to the increased resistance to imipenem in the isolate IRP41. Furthermore, a ldcA (PA5198) gene, encoding murein tetrapeptide carboxypeptidase, has been demonstrated for the first time to negatively influence the ampC expression in P. aeruginosa.